2020
DOI: 10.1055/s-0040-1709500
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Clinical Presentation and Angiographic Findings in Patients with Ischemia and No Obstructive Coronary Artery Disease (INOCA): A Single-Center Observational Registry

Abstract: Ischemia and no obstructive coronary arteries (INOCA) is a common clinical presentation, with a variety of causes that are often not fully investigated in routine clinical practice. The goal of our study was to characterize a real-world population of patients with INOCA, with a deeper focus on symptoms and stress test findings. The study population consisted of 435 patients who underwent diagnostic coronary angiography for anginal symptoms and/or evidence of myocardial ischemia at non-invasive imaging. In all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Unlike our significant findings for increased frequency of chest pressure, shortness of breath, and fatigue/weakness/faintness among women with INOCA (all having p < 0.001), as well as a higher frequency trend for symptom aggravation by very hot/cold weather among women with obstructive CAD ( p = 0.025); women of the KoROSE study had no differences between groups for pressure ( p = 0.513), dyspnea ( p = 0.259), syncope ( p = 0.552), and aggravation by low temperature ( p = 0.225) [ 24 ]. Dyspnea was significantly associated with INOCA among both men and women ( p < 0.001) in the CIAO-ISCHEMIA study [ 25 ], and UK investigators [ 26 ] reported a statistical trend for shortness of breath among females with INOCA (12%); however, their comparison group was men with INOCA (6.6%; p = 0.046), using a <70% cutoff [ 26 ]. Our finding of significantly increased fatigue/weakness/faintness among women with INOCA is echoed similarly in a secondary analysis of vital exhaustion among 3656 women with INOCA from the Danish prospective multicenter iPOWER study [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike our significant findings for increased frequency of chest pressure, shortness of breath, and fatigue/weakness/faintness among women with INOCA (all having p < 0.001), as well as a higher frequency trend for symptom aggravation by very hot/cold weather among women with obstructive CAD ( p = 0.025); women of the KoROSE study had no differences between groups for pressure ( p = 0.513), dyspnea ( p = 0.259), syncope ( p = 0.552), and aggravation by low temperature ( p = 0.225) [ 24 ]. Dyspnea was significantly associated with INOCA among both men and women ( p < 0.001) in the CIAO-ISCHEMIA study [ 25 ], and UK investigators [ 26 ] reported a statistical trend for shortness of breath among females with INOCA (12%); however, their comparison group was men with INOCA (6.6%; p = 0.046), using a <70% cutoff [ 26 ]. Our finding of significantly increased fatigue/weakness/faintness among women with INOCA is echoed similarly in a secondary analysis of vital exhaustion among 3656 women with INOCA from the Danish prospective multicenter iPOWER study [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women have at least the double expected prevalence of ischaemia from INOCA as confirmed from coronary angiography in comparison to men . In a study of INOCA including patients with stable angina, 70.2% of female versus 43.1% of male patients had coronary microvascular dysfunction (CMD) or epicardial artery vasospasm [ 41 , 42 ] .…”
Section: Inocamentioning
confidence: 99%
“…It is characterized by a range of symptoms, including chest pain, palpitation, and breathlessness [1][2][3] . However, half of patients do not have significant organic stenosis (≥ 50%) of epicardial coronary arteries who undergo coronary angiography (CAG) for clinical symptoms likely to angina or possible myocardial ischemia [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a range of symptoms, including chest pain, palpitation, and breathlessness [1][2][3] . However, half of patients do not have significant organic stenosis (≥ 50%) of epicardial coronary arteries who undergo coronary angiography (CAG) for clinical symptoms likely to angina or possible myocardial ischemia [4][5][6] .In 2017, Bairey et al coined the term ischemia with nonobstructive coronary artery disease (INOCA) 7) , and INOCA has since received increased clinical attention worldwide. In 2020, the European Association of Percutaneous Cardiovascular Intervention (EAPCI) proposed the first expert consensus regarding INOCA, which recommended a universal defi nition 8) .…”
mentioning
confidence: 99%